Upside potential of hedge funds as a predictor of future performance - Bali, Turan G.; Brown, Stephen J.; Caglayan, Mustafa O. (Journal of Banking & Finance, 2019)
ABSTRACT This paper investigates the relationship between upside potential and future hedge fund returns. We measure upside potential based on the maximum monthly returns of hedge funds (MAX) over a fixed time interval, and show that MAX successfully predicts cross-sectional differences in future fund returns. Hedge funds with strong upside potential generate 0.70% per month higher average returns than funds with weak upside potential. After controlling for alternative risk and performance measures, funds’ market-timing ability, and a large set of fund characteristics, the positive link between MAX and future returns remains highly significant. We conclude that MAX, as a simple proxy for realized noln-normalities in hedge funds, offers incremental information on future hedge fund returns above and beyond provided by standard risk, performance, and market-timing measures.